AC ELECTRIC TRANSPORT PROPERTIES OF Zn SUBSTITUTED Li FERRITES - M. H. Mesbah Ahmed; Shamima Choudhury; A. K. M. Akther Hossain (European Scientific Journal, ESJ, 2014)
The electrical transport properties of ZnxLi0.45-x/2Fe2.55-x/2O4 (where, x=0.0, 0.3, 0.5) synthesized by conventional ceramic method have been investigated as a function of Zn content. The X-ray analysis confirms the formation of single phase cubic spinel structure. The ac resistivity and dielectric constant show opposite trend with increase in Zn content. The ac resistivity and dielectric constant of the samples are found to decreases with increase in frequency, exhibiting normal ferromagnetic behaviour. Dielectric constant of the samples decreases rapidly at lower frequencies and slower at higher frequencies which may be due to the Maxwell-Wagner interfacial polarization. The electrical properties can be explained on the basis of Fe2+/Fe3+ ionic concentration.